An Effective Go-Back-N Automatic-Repeat-Request Scheme for Variable-Error-Rate Channels - Kosut, P.; Polec, J.; Diaz, P.; Menhart, P. (Radioengineering Society, 1999)
In non stationary channels, error rates vary considerably. This paper proposes an effective go-back-N (GBN) Automatic-Repeat-Request (ARQ) scheme which estimates the channel state in a simple manner, and adaptively switches its operation mode. It provides higher throughput than other comparable ARQ schemes in conditions of Land-Mobile-Satellite (LMS) channel.
Keywords: channel; model; Automatic-Repeat-Request; ARQ; Land-Mobile-Satellite; LMS